Can rutin ameliorate aluminum phosphide-induced acute cardiac toxicity in adult albino rats? - M. Abo El Wafa, Sahar; A. El Noury, Heba (International Journal of Pharmacology and Toxicology, 2020)
Current management of rice tablet or aluminium phosphide (AlP) poisoning has remained mostly supportive despite of its fatal outcome and unfortunately no antidote is found yet, therefore, there is a need to search for a treatment that can adequately protect against its toxicity. To the best of our knowledge, there are no studies until now concerning the cardioprotective effect of rutin against AlP cardiac toxicity in rats. For this purpose, this study was carried out to investigate the possible protective effect of rutin against AlP induced cardiotoxicity in rats. Forty male albino rats were randomly divided into four groups. Group I: normal control group was served as untreated rats and received distilled water orally through a gastric tube. Group II: Rutin treated group received a dose of 100 mg/kg rutin dissolved in distilled water and given orally through a gastric tube. Group III: AlP intoxicated rats received AlP oral single sub-lethal dose (2 mg/Kg body weight) dissolved in distilled water and given through a gastric tube. Group IV: AlP intoxicated rats + Rutin treated one hour after receiving AlP in doses as mentioned above. After that we tested the following parameters: ECG changes including HR and ST-segment elevation, serum level of TNF-Î±, IL-6 and H-FABP (pg/ml), antioxidant and Oxidant parameters in cardiac tissue as GSH, SOD, and MDA, apoptotic factor caspase-3 and histopathological examination of cardiac tissue was also included. The results showed that treatment with rutin caused a significant decrease in heart rate and ST segment elevation, a significant decrease in activity of TNF-Î± and IL-6 and levels of H-FABP also a significant decrease in the activity of SOD with decreased levels of MDA and caspase-3 level and a significant increase in the level of GSH compared to (AlP) intoxicated group, also histopathological changes induced by AlP improved after treatment with rutin. It is concluded that AlP intoxication caused ECG, biochemical and histopathological changes which were potentially improved with rutin.Â Â
Keywords: Acute; Aluminum Phosphide (Alp); Cardiac Toxicity; Rats; Rutin.